Adaptive flow assignment for CO2 transcritical power cycle (CTPC): An engine operational profile-based off-design study. (15th June 2021) - Li, Ligeng; Tian, Hua; Shi, Lingfeng; Wang, Jingyu; Li, Min; Shu, Gequn
Abstract: CO2 transcritical power cycle (CTPC) is regarded as a promising energy conservation means in engine waste heat recovery. One of the most significant characteristics that should be noted is the considerable variation of waste heat caused by the variable engine operating conditions. Hence, the ability to follow the heat-sources variation should be enhanced to maximize its energy-saving potential. In this paper, an effective and efficient approach is proposed to deal with the different degree of variability of heat sources through a novel CTPC system configuration controlling the internal mass flow rate of the working fluid actively. An adaptive flow assignment strategy is also developed to enhance the ability to follow the heat-sources variation. A comprehensive input-optimization-output framework is constructed consisting of performances analysis under both design and off-design procedures. Results show that the CTPC adaptation to the heat-sources variation can be effectively improved with the proposed system and operational strategy. Promising energy-saving potential is found when the proposed system and strategy with adaptive flow assignment are implemented. The effective operating conditions are expanded from 8 to 22 points based on the engine operational profile, and the net generated power is increased by 47.5% considering the European stationary cycle (ESC) 13-mode. Highlights: Strategy with adaptive flow assignment strongly improves applicability to heat sources variation. A novel configuration of CO2 power cycle with additional split branch is proposed. A three-level evaluation framework is developed considering engine operational profile. Maximum engine brake thermal efficiency can be improved by 6.68% compared with baseline. Net generated power with proposed strategy is increased by 47.5% under European stationary cycle.